Investigation of Oxidative Stress Levels in Cats with Chronic Kidney Disease - Şahin, B; Duran, U; Küllük, E; Çenesiz, S; Dalğın, D (Journal of the Hellenic Veterinary Medical Society, 2025)
The exact mechanism of oxidative stress caused by CRF is not understood. This study aimed to examine the oxidative stress levels and some biochemical parameters of cats diagnosed with CRF and to investigate the mechanism of oxidative stress formation. 30 cats diagnosed with CRF formed the CRF group, and 10 healthy cats formed the control group. For biochemical analyses, blood samples taken from the Vena cephalica antebrachii of cats were centrifuged. Serums were removed and analyses were carried out. Among these analyses, biochemical parameters such as symmetric dimethylarginine (SDMA), malondialdehyde (MDA), total antioxidant status (TAS), total oxidant status (TOS), and oxidative stress index (OSI) and urea, creatinine, ALT, AST, and ALP were examined. According to the findings of the study, while TAS levels were found to be low in cats diagnosed with CRF (P<0.05), TOS, OSI, MDA, and SDMA levels were found to be high (P<0.05). In addition, urea, creatinine values, ALP, and AST activity were found to be higher in cats diagnosed with CRF than in healthy cats (P<0.05), while ALT activity did not change (P>0.05). These findings indicate that CRF is associated with increased oxidative stress in cats and that certain biochemical parameters can be used in the diagnosis of CRF. Therefore, it is thought that oxidative stress is important in the pathophysiology of CRF and that the progression of the disease can be kept under control by playing an important role in the diagnosis, monitoring, and treatment planning of renal failure.